Secular trends in HIV knowledge and attitudes among Vietnamese women based on the Multiple Indicator Cluster Surveys, 2000, 2006, and 2011: what do we know and what should we do to protect them? - Nguyen Van Huy; Hwa-Young Lee; You-Seon Nam; Nguyen Van Tien; Tran Thi Giang Huong; Luu Ngoc Hoat (Taylor & Francis Group, 2016)
Background: In Vietnam, women are at risk of HIV infection due to many factors. However, there is limited evidence about what women know and how they behave to protect themselves from HIV. Objective: The objective of this study was to investigate the trends in comprehensive HIV/AIDS knowledge, attitude, and associated factors among Vietnamese women from 2000 to 2011. Design: Data from three waves of the Vietnam Multiple Indicator Cluster Surveys (years 2000, 2006, and 2011) were used. Logistic regression methods examined factors associated with each of two dependent variables, HIV/AIDS knowledge and attitude toward HIV/AIDS. Results: Although there was an increasing trend in basic HIV/AIDS knowledge and positive attitude toward the disease, in Vietnamese women in the general population over the survey years, the prevalence of women with basic HIV/AIDS knowledge and positive attitude toward HIV/AIDS was low. Multivariable models indicated that women who had higher levels of education, lived in urban areas, had higher economic status, and knew about places of HIV-related services were more likely to have good HIV/AIDS knowledge (e.g. in 2011, AOR's=3.01; 1.27; 1.88; 2.03, respectively). Women with higher educational attainment, knew about HIV services, and had better HIV knowledge were more likely to report positive attitude toward HIV/AIDS (e.g. in 2011, AOR's=2.50; 1.72; 2.23, respectively). Conclusions: This study recommends that public health programs for the control of HIV, such as behavioral change communication campaigns or social policies for women, should focus not only in improving the quality of existing HIV/AIDS counseling and testing services but also on expanding coverage to increase accessibility to these services for women in rural areas. In addition, efforts to raise the level of knowledge about HIV/AIDS and improve attitude toward the disease should be undertaken simultaneously. The results of this study can help inform HIV control policies and practices in other developing countries.